An assessment of Gender Equality and Social Inclusion (GESI) in the governance, policies and programs of Bangladesh’s agri-food systems - Irfanullah, H. Md.; Garrett, J.; Joshi, Deepa; Wickramasinghe, Nipuna (International Water Management Institute (IWMI). CGIAR Initiative on Asian Mega-Deltas, 2023)
Agri-food system policies and programs in Bangladesh increasingly consider environmental challenges and intersections. Social and political dimensions of agri-food systems are of equal importance to sustainable food security. Is similar attention paid to these issues? The impacts of climate change and challenges from environmental pollution and degradation of natural resources have been shown to lead to declines in agricultural productivity, while at the same time further impacting sustainability and ecosystem services. These challenges can worsen food insecurity in Bangladesh. Inattention to these issues in policies, programs and fiscal strategies will not only affect those who are the most marginalized but also undermine Bangladesh’s social and economic development goals, including the Sustainable Development Goals (SDGs).